(untitled) (Journal of Medical & Health Sciences Review, 2025)
Psidium guajava (guava) is a tropical plant renowned for its ethnomedicinal properties. This study aimed to conduct a comprehensive investigation of the phytochemical constituents and antioxidant potential of guava leaf extracts using multiple in vitro models. Leaves collected from the Charsadda region were sequentially extracted using n-hexane, chloroform, and methanol. The extracts were evaluated for qualitative and quantitative phytochemistry, including total phenolic content (TPC) and total flavonoid content (TFC). Antioxidant activity was assessed using four different assays: DPPH, ABTS, Ferric Reducing Antioxidant Power (FRAP), and a Phosphomolybdenum assay for total antioxidant capacity (TAC). The methanol extract yielded the highest extractive value (9.85%) and contained the highest levels of TPC (185.42 ± 4.86 mg GAE/g) and TFC (92.75 ± 3.12 mg QE/g). Phytochemical screening confirmed the presence of flavonoids, phenols, terpenoids, steroids, and saponins in the methanol extract. In all antioxidant assays, the methanol extract demonstrated superior, dose-dependent activity, with an IC₅₀ of 46.18 ± 1.45 µg/mL in the DPPH assay, significantly lower than the other extracts. A strong positive correlation (R² > 0.95) was observed between TPC/TFC and antioxidant activity. The study conclusively establishes that the methanol extract of P. guajava leaves is a rich source of natural antioxidants, primarily phenolics and flavonoids, validating its traditional use and potential for nutraceutical development.